Clinical and Ultrasound Sequelae of Nonvisualized Calf Veins on Duplex Ultrasound for Suspected Deep Vein Thrombosis. Issue 1 (March 2016) - Henry, Jon C.; Strosberg, David; Warhadpande, Shantanu; Satiani, Bhagwan; Go, Michael R.
Objectives: Calf veins are not visualized in up to 40% of lower extremity venous duplex ultrasounds (DUS). Little is known about the clinical implications of nonvisualized calf veins. We sought to investigate the incidence of nonvisualized calf veins, rate of subsequent venous thromboembolism (VTE), and factors influencing successful visualization on subsequent DUS. Methods: We reviewed all patients who had DUS in 2012 at our institution who had nonvisualized calf veins, no deep vein thrombosis (DVT), and available follow-up. Demographics, Well's score, body mass index (BMI), indication for DUS, activity level, reason for nonvisualization, initial and subsequent DUS results, and subsequent occurrence of VTE were collected. Results: A total of 8, 237 DUS were performed in 2012. Of these, 891 (10.8%) DUS in 717 patients had at least one nonvisualized calf vein. Seven hundred twenty-eight limbs (484 patients) had no DVT and had available follow-up and comprised the study population. The most common reasons for nonvisualization were edema (35.5%) and body habitus (31.8%). Twenty-two (4.5%) patients were subsequently identified to have VTE; 9 limbs had only pulmonary emboli, 12 had only DVT, and 1 had both. Only length of stay in the hospital correlated with the development of VTE. One hundred forty-eight of the 484 patients had subsequent DUS at a median of 2.43 months; 45.3% of subsequent DUS successfully imaged the previously nonvisualized veins. Whole lower extremity swelling, single vein nonvisualization, and single limb nonvisualization at initial DUS were associated with successful visualization on subsequent DUS. Thirteen (8.8%) new DVT were seen on subsequent DUS, six were seen in calf veins that previously were not visualized, and seven were seen in either femoropopliteal veins or calf veins that previously were visualized and did not have thrombus. Conclusions: Non-visualized calf veins are common in DUS. Almost half of patients with nonvisualized veins on initial DUS had successful visualization on subsequent DUS. Whole lower extremity swelling, single vein nonvisualization, and single limb nonvisualization at initial DUS were associated with successful visualization on subsequent DUS. In all, 4.1% of patients with nonvisualized veins on initial DUS go on to develop VTE and 8.8% of patients who have subsequent DUS are found to have DVT. When initial DUS is unable to visualize calf veins, selective repeat DUS may be useful to identify either new or initially unseen DVT.